1994
DOI: 10.1073/pnas.91.8.3058
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic disinhibition during maintenance of long-term potentiation in the CA1 hippocampal subfield.

Abstract: Long-term potentiation (LTP) in the CA1 region of the hippocampus is widely believed to occur through In spite of the attention excitatory transmission processes have received in connection with LTP, potentiation of excitatory responses after tetanization could theoretically occur through impairment of synaptic inhibition. Type A y-aminobutyric acid (GABAA) receptor-mediated synaptic inhibition plays a critical role in the control of excitation in the mammalian central nervous system (6). Several studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 35 publications
4
59
0
Order By: Relevance
“…However, the present results suggest that L-LTP may be pathway dependent. In fact, in several original LTP studies in the hippocampus, the failure of LTP induction has been reported (between 57.9 and 85.2% success rate) (Chavez-Noriega et al, 1990;Clark and Collingridge, 1995;Malinow and Tsien, 1990;Stelzer et al, 1994;Wheal et al, 1983). Second, we found that L-LTP induction triggered the recruitment of cortical circuit.…”
Section: Discussionmentioning
confidence: 52%
“…However, the present results suggest that L-LTP may be pathway dependent. In fact, in several original LTP studies in the hippocampus, the failure of LTP induction has been reported (between 57.9 and 85.2% success rate) (Chavez-Noriega et al, 1990;Clark and Collingridge, 1995;Malinow and Tsien, 1990;Stelzer et al, 1994;Wheal et al, 1983). Second, we found that L-LTP induction triggered the recruitment of cortical circuit.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, exogenous GABA when paired with postsynaptic depolarization also produced LTT. LTT contributes to pairing-induced LTP but differs from changes previously observed for GABAergic synapses after LTP (23)(24)(25). Both LTT and pairing-induced LTP were prevented by 1 ,uM anandamide.…”
Section: Resultsmentioning
confidence: 64%
“…For instance, either LTD of IPSPs or a change in excitability likely underlies the cases of E-S potentiation that have been reported to occur in the absence of LTP (Bliss and Lomo, 1973;Andersen et al, 1980;Abraham et al, 1985;Taube and Schwartzkroin, 1988;Jester et al, 1995). Nonetheless, whereas E-S potentiation is reliably observed in the hippocampus after tetanus-LTP, studies addressing the issue of tetanus-induced plasticity in the inhibitory branch of the disynaptic circuit have reported a variety of results (McLean et al, 1996;McBain and Maccaferri, 1997;McBain et al, 1999;Gaiarsa et al, 2002), ranging from no changes in inhibition , to LTP of IPSPs (Kairiss et al, 1987;Stelzer et al, 1994;Ouardez and Lacaille, 1995;Xie et al, 1995;Maccaferri and McBain, 1996;Cowan et al, 1998;Shew et al, 2000;Perez et al, 2001) to LTD of IPSPs (McMahon and Kauer, 1997;Lu et al, 2000;Chevaleyre and Castillo, 2003). Although we argue that inhibitory plasticity does not contribute to E-S potentiation when using a relatively mild pairing protocol, it may play a significant role under other induction protocols that more strongly engage the inhibitory circuitry.…”
Section: Mechanisms Underlying E-s Potentiationmentioning
confidence: 99%